A selective image encryption scheme using LICC hyperchaotic system. Issue 12 (30th June 2022) - Wei, Chengjing; Li, Guodong
Abstract: In this paper, an improved multi‐dimensional hyperchaotic system derived from the logistic map and the ICMIC based on closed‐loop coupling (LICC hyperchaotic system) is proposed and it is used in the design of selective image encryption. The performance analysis shows that the LICC hyperchaotic system with a strong coupling degree has parameters whose value can be set more flexibly and can generate a wider and more uniform distribution of chaotic sequences. Then selective image encryption is proposed. Firstly, an adaptive pseudo‐random sequence generator based on hash function is designed to ensure the difference of sequences used in different encryption steps. Second, a novel bit‐level scrambling is designed to increase the encryption speed. Finally, an efficient rule to select image blocks with weak security is proposed and the second step of the encryption is performed at the selected blocks of the image to ensure security. The encryption performance and security analysis show that the proposed encryption algorithm based on an improved hyperchaotic system is secure enough to resist several types of attacks.